The Sanctuary of Aphrodite and Ares (Paus. 2.25.1) in the Periurban Area of Argos and Temples with a Double Cella in Greece - Fusco, Ugo (Tekmeria, 2017)
The object of this study is the analysis of the sanctuary with a double cella or double temple (ἱερὸν διπλοῦν) dedicated to Aphrodite and Ares in the periurban area north-west of Argos. Within the context of studies on Greek architecture, a specific analysis of the typology of cult structures with a double cella is still lacking, since the attestations have hitherto been considered too limited. The present study, still ongoing, has uncovered a complex situation and the archaeological attestations recovered are not as limited as thought in the past. Hitherto, around twenty examples have been collected, without considering uncertain cases, for which the limited data available have rendered a precise interpretation impossible. The only direct source on the Argive sanctuary of Aphrodite and Ares is the short description provided by Pausanias (2.25.1), whilst its location, ground plan, elevation, chronology and architectural and sculptural decoration remain essentially unknown. New observations may help clarify some of the issues that remain unresolved. The closest archaeological parallel, at least from the point of view of the ground plan, in the absence of information on the dimensions of the monument, is without doubt the temple of Venus and Roma in Rome, built by the emperor Hadrian (AD 117-138), with which the Argive temple also shares the same east-facing orientation of the cella dedicated to the goddess Aphrodite-Venus.